Six-minute walk test protocol variations in low-resource settings - A scoping review - Brittany L. Fell; Susan Hanekom; Martin Heine (AOSIS, 2021)
Background: The 6-min walk test (6MWT) is a validated tool, of submaximal intensity, used to objectively measure functional exercise capacity. In 2002, the American Thoracic Society (ATS) developed guidelines on standardising the implementation of the 6MWT. Despite the relative ease of conducting the 6MWT as per these guidelines, adaptations are implemented. Objectives: Identify (1) what 6MWT adaptations to the ATS guidelines have been described in low-resource settings (LRS), (2) the purpose of the adapted 6MWT and (3) the reported argumentation for making these adaptations in relation to the specific context. Methods: Five databases were searched from inception until February 2021. Studies that adapted and conducted the 6MWT in LRS were included. Data concerning the study source, participants, 6MWT: purpose, variations, outcome and rationale were extracted. Results: A total of 24 studies were included. The majority of studies (n = 18; 75%) were conducted in lower-middle income countries. The most common adaptation implemented was variation to course length. Eight studies provided a rationale for adapting the 6MWT. Space constraint was the most common reason for adaptation. Conclusion: The most common reason (space constraints) for adapting the 6MWT in LRS was addressed through adaptations in course length and/or configuration. The results of this review suggest that the value of the ATS-guided 6MWT in LRS may need to be re-evaluated. Clinical implications: Using adapted forms of the 6MWT may lead to an underestimation of a patient's abilities, misinformed discharge and developing inappropriate exercise programmes. Additionally, diverting from ATS guidelines may affect the continuity of care.